Effect of three‐dimensional porosity gradients of biomimetic coatings on their bonding strength and cell behavior. Issue 5 (24th July 2020) - Yu, Le; Silva Santisteban, Tomas M.; Liu, Qinqing; Hu, Changmin; Bi, Jinbo; Wei, Mei
Abstract: Surface modification techniques are often used to enhance the properties of Ti‐based materials as hard‐tissue replacements. While the microstructure of the coating and the quality of the interface between the substrate and coating are essential to evaluate the reliability and applicability of the surface modification. In this study, both a hydroxyapatite (HA) coating and a collagen‐hydroxyapatite (Col‐HA) composite coating were deposited onto a Ti‐6Al‐4V substrate using a biomimetic coating process. Importantly, a gradient cross‐sectional structure with a porous coating toward the surface, while a dense layer adjacent to the interface between the coating and substrate was observed in three‐dimensional (3D) from both the HA and Col‐HA coatings via a dual‐beam focused ion beam‐scanning electron microscope (FIB‐SEM). Moreover, the pore distributions within the entire coatings were reconstructed in 3D using Avizo, and the pores size distributions along the coating depth were calculated using RStudio. By evaluating the mechanical property and biocompatibility of these materials and closely observing the cross‐sectional cell‐coating‐substrate interfaces using FIB‐SEM, it was revealed that the porous surface created by both coatings well supports osteoblast cell adhesion while the dense inner layer facilitates a good bonding between the coating and the substrate. Although the mechanical property of the coating decreased with the addition of collagen, it is still strong enough for implant handling and the biocompatibility was promoted.